1978
DOI: 10.1002/bbpc.197800128
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Changes of Light Absorption by the Electric Field of the Electrolytic Double Layer

Abstract: The optical properties of molecules adsorbed on a metal/electrolyte interface depend on the electric field across the double layer. The changes with the electrode potential can be measured by modulation reflection spectroscopy. This provides a method for measuring specifically optical properties of the adsorption layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Instead of measuring an electrical signal (e.g., current and charge), one could also study electrochemical reactions via optical detection . Studies have found that electrochemical reactions are accompanies by changes in optical properties, such as reflectivity of an electrode. However, the reflectivity changes are often small. To amplify the optical signal, an interferometric method has been used to study electrochemical reactions via detecting changes in the refractive index in the electrolyte. The interferometric method measures both changes on the electrode surface and in the electrolyte, which cannot be easily deconvoluted.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of measuring an electrical signal (e.g., current and charge), one could also study electrochemical reactions via optical detection . Studies have found that electrochemical reactions are accompanies by changes in optical properties, such as reflectivity of an electrode. However, the reflectivity changes are often small. To amplify the optical signal, an interferometric method has been used to study electrochemical reactions via detecting changes in the refractive index in the electrolyte. The interferometric method measures both changes on the electrode surface and in the electrolyte, which cannot be easily deconvoluted.…”
Section: Introductionmentioning
confidence: 99%
“…The potential modulated ER spectrum due to an adsorbate molecule could also originate from direct charge-electric field interaction (electrochromism). This type of response is usually obtained at electrode potentials that are far from the redox value, and has a shape corresponding to the first derivative of the absorption spectrum of the adsorbate (23,27). The characteristics of the ER spectra reported in this work suggest that they are not related to electrochromism.…”
Section: Resultsmentioning
confidence: 76%
“…For our detection sensitivity (DR/R Ç 10 06 ), it is feasible to follow these The differential reflectance measures the difference in reflection between the case when a protein layer is present on charge transfer reactions even at submonolayer quantities of Pdx adsorbate since the difference in the absorption spectra between the two redox forms, Pdx ox and Pdx red , is substantial. Similar optical detection of faradaic transitions has been reported recently for adsorbed organic dyes (22)(23)(24)(25), metal porphyrins (27), and heme proteins (10,11,26).…”
Section: Optical Foundations Of Electroreflection Measurementmentioning
confidence: 64%
“…Consequently, the band shift effect seems to be absent in the optical response of the adsorbed methylene blue. According to the theory derived by Liptay [25] and Plieth et al [26], the band shift effect can be expressed by equations as follows: ENERGY,,.= (I/J;] -]p./()(cos +)F+ ENERGY,=,…”
Section: High Coveragementioning
confidence: 99%
“…A linear dependence of the wave function and the transition moment on the field strength is predicted by first-order perturbation theory. The analysis of this effect applied to the electrochemical interphase leads to relationships that depend linearly on either the modulation amplitude or both the modulation amplitude and the bias potential [26].…”
Section: F=f+b(e-e+) (3)mentioning
confidence: 99%